Cloning And Expression Of Synthetic Human Erythropoietin In Methylotrophic Yeast, Pichia Pastoris - Bustami, Yazmin (2010)

(untitled)
Human erythropoietin is a hormone or glycoprotein produced by the kidney and bone marrow with important physiological functions, such as, erythropoiesis, angiogenesis, and wound healing. The natural source of huEpo is purified from human urine (uhuEPO). Alternatively, recombinant human erythropoietin could overcome the limited supply of uhuEPO. Thus, the focus of this study is to generate a synthetic huEPO gene and express in Pichia pastoris. PCR assembly method utilized to construct a synthetic gene using twenty sets of overlapping oligonucleotides, covering the huEPO A gene sequence and two newly introduced restriction enzyme sites. Results from DNA sequence analysis showed accurate assembled synthetic huEPO gene albeit minor base mutations detected.